Intergenerational Community Learning Management for Business Sustainability in Traditional Food MSMEs: A Case Study of the Kecimpring Enterprise Community in Indonesia - Dadang Yunus Lutfiansyah Dadang; Didin Samsudin; Sodikin; Hanifah Irnawati; Cucu Sukmana; Aqeel Khan (Journal of Nonformal Education, 2026)
Background – Traditional food MSMEs play an important role in preserving local heritage and supporting community livelihoods. However, many family-based enterprises face sustainability challenges due to weak succession and ineffective intergenerational knowledge transfer. Research Urgency – Existing studies generally examine knowledge transfer, succession, and business sustainability separately, providing limited understanding of how community learning supports business continuity across generations. Research Objectives – This study aims to develop an Intergenerational Community Learning Management (ICLM) Model that facilitates knowledge transfer and business sustainability in traditional food MSMEs. Research Method – A qualitative case study was conducted in the Kecimpring traditional snack enterprise community in Pagerwangi Village, West Bandung Regency, Indonesia. Data were collected through in-depth interviews, participant observation, documentation, and literature review involving five purposively selected participants. Data were analyzed using Miles, Huberman, and Saldaña’s interactive model and thematic analysis. Research Findings – Business sustainability is supported by environmental scanning, community capacity building, tacit and explicit knowledge transfer, mentoring, and succession learning. These processes occur through four stages: observation, apprenticeship, guided practice, and independent production. Knowledge transfer is bidirectional, with senior artisans transmitting craft expertise while successors contribute digital marketing knowledge. The proposed ICLM model integrates inputs, processes, outputs, and outcomes to support intergenerational business sustainability. Research Conclusion – Community learning is a strategic mechanism for sustaining traditional MSMEs through knowledge continuity and successor development. Research Novelty/Contribution – This study introduces the ICLM Model, extending nonformal education literature by integrating community learning, knowledge transfer, succession, and business sustainability within a unified framework.